A Trigonal Prismatic Cobalt(II) Complex as a Single Molecule Magnet with a Reduced Contribution from Quantum Tunneling. Issue 8 (5th April 2019) - Pavlov, Alexander A.; Aleshin, Dmitry Y.; Savkina, Svetlana A.; Belov, Alexander S.; Efimov, Nikolay N.; Nehrkorn, Joscha; Ozerov, Mykhaylo; Voloshin, Yan Z.; Nelyubina, Yulia V.; Novikov, Valentin V.
Abstract: Herein, we report a new trigonal prismatic cobalt(II) complex that behaves as a single molecule magnet. The obtained zero‐field splitting, which is also directly accessed by THz‐EPR spectroscopy (−102.5 cm −1 ), results in a large magnetization reversal barrier U of 205 cm −1 . Its effective value, however, is much lower (101 cm −1 ), even though there is practically no contribution from quantum tunneling to magnetization relaxation. Abstract : Molecular magnetism : A cobalt(II) acetylmethylimidazole‐oximate clathrochelate behaves as a single molecule magnet according to THz‐EPR spectroscopy, magnetometry, and NMR spectroscopy